Scalar Curvatures of Invariant Almost Hermitian Structures on Generalized Flag Manifolds - Grama, Lino; Oliveira, Ailton R. (Symmetry, Integrability and Geometry: Methods and Applications, 2021)
In this paper, we study invariant almost Hermitian geometry on generalized flag manifolds. We will focus on providing examples of Kähler-like scalar curvature metric, that is, almost Hermitian structures (, ) satisfying =2C, where is Riemannian scalar curvature, and C is the Chern scalar curvature.